Trichophyton rubrum Elicits Phagocytic and Pro-inflammatory Responses in Human Monocytes Through Toll-Like Receptor 2 - Celestrino, Giovanna Azevedo; Reis, Ana Paula Carvalho; Criado, Paulo Ricardo; Benard, Gil; Sousa, Maria Gloria Teixeira (Frontiers in Microbiology, 2019)
Dermatophytosis is a superficial fungal infection mostly restricted to keratinized tissues such as skin, hair and nails, but with potential to cause invasive or even systemic disease in immunocompromised patients. Trichophyton rubrum is the main etiologic agent, accounting for approximately 80% of the cases. Mononuclear phagocytes respond to pathogens through phagocytosis followed by production of several antimicrobial molecules, such as reactive oxygen and nitrogen species, and failure in doing so may contribute to development of chronic fungal infections. Toll like receptors (TLRs) located on the surface of phagocytic cells bind either directly to target particles or through opsonizing ligands, and trigger an actin-mediated ingestion. Even though the mechanisms involved in TLR-mediated cytokine responses are well established, the contribution of TLR in the recognition of T. rubrum by adherent monocytes remains unclear. Here, we report that phagocytosis of T. rubrum conidia by adherent monocytes is mediated by TLR2. Blockade of TLR2 by neutralizing antibodies impaired the fungicidal activity of monocytes as well their secretion of tumor necrosis factor (TNF)-α, but neither nitric oxide (NO) production nor interleukin (IL) – 10 secretion were disturbed. So far, our data suggest that TLR2 is required for efficient conidial phagocytosis and the absence of TLR2 signaling in human monocytes may impair the subsequent inflammatory response. These findings expand our understanding of phagocyte modulation by this important fungal pathogen and may represent a potential target for interventions aiming at enhancing antifungal immune responses.